2007
DOI: 10.1152/ajplung.00176.2007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphologic determinants of pneumothorax in lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis, a multisystem disease affecting women, is characterized by proliferation of abnormal smooth muscle-like cells in the lungs, leading to cystic destruction of the parenchyma and recurrent pneumothoraces. Clinical characteristics of lymphangioleiomyomatosis patients were analyzed to determine the relationship of pneumothoraces to disease progression. Patients were genotyped for polymorphisms in genes of extracellular matrix proteins collagen, elastin, and matrix metalloproteinase-1 to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
2
41
1
5
Order By: Relevance
“…In agreement with prior observations, 9 we found that LAM patients who had pneumothoraces tend to have lower FEV 1 , and a CT scan pattern consisting of larger cysts scattered throughout relatively normal lung parenchyma. This suggests that the presence of larger cysts predisposes patients both to pneumothorax and greater rates of FEV 1 decline.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with prior observations, 9 we found that LAM patients who had pneumothoraces tend to have lower FEV 1 , and a CT scan pattern consisting of larger cysts scattered throughout relatively normal lung parenchyma. This suggests that the presence of larger cysts predisposes patients both to pneumothorax and greater rates of FEV 1 decline.…”
Section: Discussionsupporting
confidence: 93%
“…For LAM and IPF patients, the severity of lung disease and cyst size were graded semiquantitatively by CT scans, as previously described. 8,9 Patients who had 1 to 10 cysts were placed in the category of minimal disease (grade 0). If Ͼ 10 cysts were identified, the lungs were divided in three zones (upper, middle, and lower).…”
Section: Chest Roentgenograms and Ct Scansmentioning
confidence: 99%
“…Levels of different MMPs were elevated in urine and lung nodules of LAM patients [150], and analysis of LAM tissue from lung biopsies indicated elevated reactivity of MMP2 and MMP9, but not of TIMP1 and TIMP2 [151]. MMP1 was suggested as a modifier gene affecting changes in the ECM that result in greater susceptibility to pneumothorax and rate of decline in lung function [152]. Consequently, MT1-MMP, an activator of MMP1, was also associated with proliferating LAM cells [153].…”
Section: Dysregulation Of Mmps In Different Lung Disorders and Its Thmentioning
confidence: 97%
“…Lung cysts are the hallmark lesion in LAM and are present in all patients ( fig. 2) [29,30]. Their appearance, size and contour vary considerably typically ranging from 2-5 mm in diameter but occasionally as large as 30 mm [31,32].…”
Section: Radiological Criteria For Diagnosismentioning
confidence: 99%